2020
DOI: 10.15252/embj.2019104347
|View full text |Cite
|
Sign up to set email alerts
|

Steroid‐dependent switch of OvoL/Shavenbaby controls self‐renewal versus differentiation of intestinal stem cells

Abstract: Adult stem cells must continuously fine‐tune their behavior to regenerate damaged organs and avoid tumors. While several signaling pathways are well known to regulate somatic stem cells, the underlying mechanisms remain largely unexplored. Here, we demonstrate a cell‐intrinsic role for the OvoL family transcription factor, Shavenbaby (Svb), in balancing self‐renewal and differentiation of Drosophila intestinal stem cells. We find that svb is a downstream target of Wnt and EGFR pathways, mediating their activit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 82 publications
4
28
0
Order By: Relevance
“…Consistently, we found that pri epidermal expression during both embryogenesis and metamorphosis is activated in response to ecdysone (Chanut-Delalande et al, 2014). Recent studies further show that pri expression is also controlled by ecdysone in the embryonic tracheal cells (Taira et al, 2021), as well as in the adult stem cells that regenerate the gut (Al Hayek et al, 2021) and kidneys (Bohère et al, 2018) to ensure homeostasis of vital functions across adulthood.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistently, we found that pri epidermal expression during both embryogenesis and metamorphosis is activated in response to ecdysone (Chanut-Delalande et al, 2014). Recent studies further show that pri expression is also controlled by ecdysone in the embryonic tracheal cells (Taira et al, 2021), as well as in the adult stem cells that regenerate the gut (Al Hayek et al, 2021) and kidneys (Bohère et al, 2018) to ensure homeostasis of vital functions across adulthood.…”
Section: Introductionsupporting
confidence: 86%
“…Recent studies have revealed that ecdysone signaling is essential to adapt the behavior of intestinal stem cells in adult females, as part of a post-mating response (Ahmed et al, 2020;Zipper et al, 2020). We found that Pri peptides are playing an important role in this ovary-to-gut interorgan communication, being able to substitute for ecdysone signaling in intestinal stem cells (Al Hayek et al, 2021). Hence, Pri peptides appear as key mediators of ecdysone, in a broad variety of tissues throughout development, as well as in adult stem cells.…”
Section: Pri Is a Core Element Of The Response To Ecdysonementioning
confidence: 71%
See 1 more Smart Citation
“…Both SP and Ecdysone directly promote ISC proliferation and gut expansion [81,82]. Mechanistically, Ecdysone induces the expression of EGFR pathway genes (spi, krn, rho) via Eip75B [83] and promotes the Pri mediated post-translational modification of the mitogenic factor Shavenbaby [84]. Ecdysone also stimulates food intake through myosuppressin (Ms) expressing neurons mediated crop enlargement [85].…”
Section: Conclusion Future Questionsmentioning
confidence: 99%
“…In addition, systemic steroid hormones produced by the ovaries regulate the conversion between Svb inhibitors and activators. Therefore, the Svb axis allows the internal integration of local signal cues and interorgan communication to regulate the proliferation and differentiation of stem cells and has a wide range of roles in adult stem cells and cancer stem cells 128 . A recent study showed that the interaction of EMT-TFs (Snail, Zeb1/2) and the epithelial stabilizing factor Svb can regulate stemness and pEMT 129 .…”
Section: Pemt and Scc Stemnessmentioning
confidence: 99%